Strengthening laboratory capacity through the surveillance of rotavirus gastroenteritis in Central Africa: the Surveillance Épidémiologique en Afrique Centrale (SURVAC) Project. Issue 1 (16th November 2015) - Waku‐Kouomou, Diane; Esona, Mathew D.; Pukuta, Elizabeth; Gouandijka‐Vasilache, Ionela; Boula, Angeline; Dahl, Benjamin A.; Mondonge, Vital; Mekontso, David; Guifara, Gilbert; Mbary‐Daba, Regis; Lewis, Jamie; Yahaya, Ali Ahmed; et al.
Abstract: Objectives: The goal of the SURVAC pilot project was to strengthen disease surveillance and response in three countries; Cameroon (CAE), Democratic Republic of the Congo (DRC) and Central African Republic (CAR). Methods: Seven laboratories involved in rotavirus surveillance were provided with equipment, reagents and supplies. CDC and WHO staff provided on‐site classroom and bench training in biosafety, quality assurance, quality control (QC), rotavirus diagnosis using Enzyme Immunoassay (EIA) and genotyping of rotavirus strains using the Reverse Transcription Polymerase‐chain reaction (RT‐PCR). All laboratory data were reported through WHO/AFRO. Results: Twenty‐three staff members were trained on RT‐PCR for rotavirus genotyping which was introduced for the first time in all three countries. In CAE, the number of samples analysed by EIA and RT‐PCR increased tenfold between 2007 and 2013. In DRC, this number increased fivefold, from 2009 to 2013 whereas in CAR, it increased fourfold between 2011 and 2013. All laboratories passed WHO proficiency testing in 2014. Conclusion: Laboratory capacity was strengthened through equipping laboratories and strengthening a subregional laboratory workforce for surveillance of rotavirus gastroenteritis. Each of the three countries generated rotavirus surveillance and genotyping data enabling the mapping of circulating genotypes. These results will help monitor the impact of rotavirus vaccination in these countries.